Synthesis of Sumanene‐fused Acenes. Issue 11 (28th October 2022) - Nakazawa, Hironobu; Ohya, Akinobu; Morimoto, Yuto; Uetake, Yuta; Ikuma, Naohiko; Okada, Kenji; Nakano, Masayoshi; Yakiyama, Yumi; Sakurai, Hidehiro
Abstract: Sumanene derivatives fused by quinones and acenes were synthesized through Friedel‐Crafts double acylation, followed by reductive aromatization. Single‐crystal X‐ray diffraction analysis on synthesized quinone and acene derivatives revealed the one‐dimensional (1D) columnar stackings predominated by the concave‐convex alignment from sumanene moiety. The thus‐prepared sumanene‐fused acenes exhibited higher solubility to organic solvent and significant stability against aerobic oxidation than the pristine acenes. Abstract : We report a synthesis of sumanene‐fused acenes through Friedel‐Craft double acylation as well as their structural and physical properties. The products possessed higher solubility and stability than the pristine acenes, while their optical properties were almost intact. The crystal structure of the tetracene‐based one showed the one‐dimensional columnar structure, in which sumanene moieties were nicely stacked.